Experimental Research and Optimization of Parallel Condensers Dehumidifier with Temperature Control - Han Xu; Li Yong; Mao Jinfeng (Zhileng xuebao)
The shutdown reason of parallel condensers dehumidifier was analyzed. It is shown that the unbalance of the pressure in the two condensers is the main reason for shutdown, which leads to the accumulation of refrigerant and fluctuations of pressure.The advantages and shortcomings of several methods to improve the performance were discussed. The reheat condenser is proposed to be changed to evaporator when the mode turns to freezing dehumidifier. Test bench was set up and experiment was carried out.The result shows that the mode could resolve the shutdown incident. Moreover, the EER and dehumidification capacity of double evaporator mode are better than the traditional dehumidifier with one evaporator.